Dietary approaches to treat MS-related fatigue: comparing the modified Paleolithic (Wahls Elimination) and low saturated fat (Swank) diets on perceived fatigue in persons with relapsing-remitting multiple sclerosis: study protocol for a randomized controlled trial - Wahls, Terry (Trials, 2018)
BACKGROUND: Fatigue is one of the most disabling symptoms of multiple sclerosis (MS) and contributes to diminishing quality of life. Although currently available interventions have had limited success in relieving MS-related fatigue, clinically significant reductions in perceived fatigue severity have been reported in a multimodal intervention pilot study that included a Paleolithic diet in addition to stress reduction, exercise, and electrical muscle stimulation. An optimal dietary approach to reducing MS-related fatigue has not been identified. To establish the specific effects of diet on MS symptoms, this study focuses on diet only instead of the previously tested multimodal intervention by comparing the effectiveness of two dietary patterns for the treatment of MS-related fatigue. The purpose of this study is to determine the impact of a modified Paleolithic and low saturated fat diet on perceived fatigue (primary outcome), cognitive and motor symptoms, and quality of life in persons with relapsing-remitting multiple sclerosis (RRMS). METHODS/DESIGN: This 36-week randomized clinical trial consists of three 12-week periods during which assessments of perceived fatigue, quality of life, motor and cognitive function, physical activity and sleep, diet quality, and social support for eating will be collected. The three 12-week periods will consist of the following: 1. Observation: Participants continue eating their usual diet. 2. Intervention: Participants will be randomized to a modified Paleolithic or low saturated fat diet for the intervention period. Participants will receive support from a registered dietitian (RD) through in-person coaching, telephone calls, and emails. 3. Follow-up: Participants will continue the study diet for an additional 12 weeks with minimal RD support to assess the ability of the participants to sustain the study diet on their own. DISCUSSION: Because fatigue is one of the most common and disabling symptoms of MS, effective management and reduction of MS-related fatigue has the potential to increase quality of life in this population. The results of this study will add to the evidence base for providing dietary recommendations to treat MS-related fatigue and other symptoms associated with this disease. TRIAL REGISTRATION: ClinicalTrials.gov, NCT02914964. Registered on 24 August 2016. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13063-018-2680-x) contains supplementary material, which is available to authorized users.